Effectiveness and Channels of Macroprudential Instruments : Lessons from the Euro Area - Tressel, Thierry (IMF Working Papers; Working Paper ;, 2016)
The crisis has highlighted the importance of setting up macro-prudential oversight frameworks, having effective macro-prudential instruments in place to be called upon to mitigate growing financial imbalances as needed. We develop a new approach using the euro area Bank Lending Survey to assess the effectiveness of macro-prudential policies in containing credit growth and house price appreciation in mortgage markets. We find instruments targeting the cost of bank capital most effective in slowing down mortgage credit growth, and that the impact is transmitted mainly through price margins, the same banking channel as monetary policy. Limits on loan-to-value ratios are also effective, especially when monetary policy is excessively loose.